2013
DOI: 10.2166/wst.2012.615
|View full text |Cite
|
Sign up to set email alerts
|

Constructed wetlands combined with UV disinfection systems for removal of enteric pathogens and wastewater contaminants

Abstract: Water shortage is an ongoing cardinal issue in the Middle East region. Wastewater reuse offers some remediation, but to-date many rural communities in the Palestinian Authority (PA) and in Jordan are not connected to centralized wastewater treatment plants (WWTPs), many of them are disposing of their wastewater using infiltration septic tanks. This highlights the need for a small, local, low cost WWTP that can directly benefit local communities, producing effluents suitable for unrestricted irrigation. Constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 21 publications
0
14
0
6
Order By: Relevance
“…A simple integration of CTW into a recirculating hatchery was conducted by Buřič et al (Buřič et al, 2015) in the Czech Republic that different from traditional RASs which generally involve specialized technologies, such as microsieve filtration, ozonization, and UV sterilization (Azaizeh et al, 2013;Good et al, 2011;Sharrer et al, 2010;Terjesen et al, 2013). This study indicated that CTW integration has the potential to increase production (potential final biomass with CW use was estimated to be 40% greater than without CW use) of a recirculating hatchery without added operational or environmental costs.…”
Section: Constructed Treatment Wetlands Invoked For Effluent Treatmentmentioning
confidence: 98%
“…A simple integration of CTW into a recirculating hatchery was conducted by Buřič et al (Buřič et al, 2015) in the Czech Republic that different from traditional RASs which generally involve specialized technologies, such as microsieve filtration, ozonization, and UV sterilization (Azaizeh et al, 2013;Good et al, 2011;Sharrer et al, 2010;Terjesen et al, 2013). This study indicated that CTW integration has the potential to increase production (potential final biomass with CW use was estimated to be 40% greater than without CW use) of a recirculating hatchery without added operational or environmental costs.…”
Section: Constructed Treatment Wetlands Invoked For Effluent Treatmentmentioning
confidence: 98%
“…Therefore, by combining CWs with MBR, UV ( Fig. 4 (a)) or membrane chemical reactors (MCRs), for example, the effluent quality can meet the guidelines of WHO for reuse in agriculture [6,65].…”
Section: Combinations or Integrations Of Cws Targeting Other Special mentioning
confidence: 99%
“…Azaizeh et al [65] tested CWs combined with UV disinfection for removal of enteric pathogens and wastewater contaminants. CWs could remove, on average, 75% of COD and 1-2 log-unit fecal.…”
Section: Combinations or Integrations Of Cws Targeting Other Special mentioning
confidence: 99%
“…Stabilized wetland system efficiently treated the COD. The UV system coupled with the wetland was able to inactivate indicator bacteria (fecal and E. coli) to levels suitable for irrigation even at low UV transmission (Azaizeh et al, 2013).…”
Section: Nutrientsmentioning
confidence: 99%